Instruments and Methods for Cyclotron Produced Radioisotopes - Alves, Francisco; Braccini, Saverio (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The focus of this Special Issue is aimed at enhancing the discussion of Engineering Education, particularly related to technological and professional learning. In the 21st century, students face a challenging demand: they are expected to have the best scientific expertise, but also highly developed social skills and qualities like teamwork, creativity, communication, or leadership. Even though students and teachers are becoming more aware of this necessity, there is still a gap between academic life and the professional world. In this Special Edition Book, the reader can find works tackling interesting topics such as educational resources addressing students$1 (Bdevelopment of competencies, the importance of final year projects linked to professional environments, and multicultural or interdisciplinary challenges.s
English
Keywords: thick target yield; 52Mn; radioisotope production; magnetron sputtering; thorium; theranostics; molecular sieve desiccant; medical radioisotope production; vortex target; radioisotope target processing; gamma spectroscopy; solid; azeotropic mixtures; disposable kit; filament; targetry; radiopharmaceuticals; medical cyclotrons; unconventional radionuclides; radioisotope targetry; thermal study; recycling of [18O]-water; medical radioisotopes; powder target; metal 3D-printing; medical cyclotron; cyclotron; stacked-foils; copper-64; stack-foil; targets; SPECT; monitor reaction; purification; numerical analysis; carbon-11; copper-61; boron nitride nanotubes; radiometals; radioactive impurities; solid target system; Ga-68; BNNTs; spallation; recoil escape; cyclotron target; target stations; 70 MeV cyclotron; irradiation; liquid targets; target temperature; separation; solid target; enrichment grade; Molybdenum-100; cyclotron solid target; radionuclides; ion accelerator; heavy Rare Earth Elements (hREE); molybdenum material recovery